Branchinecta uruguayensis Rogers & Racz Lorenz, 2015 is a junior synonym of B. achalensis César, 1985 (Branchiopoda: Anostraca: Branchinectidae) - Cohen, Rosa Graciela; Rogers, D. Christopher (Zootaxa, 2018)
As part of preparation for identification keys to the branchiopod crustaceans of the Neotropical Region, we re-examined many species of Anostraca that appeared to be closely related. Our examination caused us to re-evaluate the status and relationship of two branchinectid species.